KAJIAN PENGGUNAAN BAHAN PEMUCAT TERHADAP KUALITAS MINYAK GORENG BEKAS KERIPIK BUAH - Moeljaningsih, Ir (UPN VETERAN JAWA TIMUR, 2010)
Cooking oil is one of nine basic commodities needed by society. Disruption of continuity of supply of products will greatly affect the prices and caused upheavals that are not desired. Various means of oil production, from how to do simple home industry through the use of technology and high costs that can only be done by big industry. On the use of cooking oil or multiple times, for example in fruit frying chips, potato chips, etc., which will cause deterioration in quality caused by the heating process with high temperature which would result in physical or chemical changes such as blackish color, embossed froth , the smell of burning, longer frying time and rancid odor that would restrict the use of cooking oil. Bleaching using a 7% weight mixture of active carbon and bleaching earth / bleaching earth (1: 3) gives the results of fruit chips used frying oil with color appearance closer to a new cooking oil.Keywords: bleaching, used frying oil